A revolution down on the farm : the transformation of American agriculture since 1929 - Conkin, Paul Keith (University Press of Kentucky, 2008)
Agriculture is the most fundamental of all human activities. Today, those who till the soil or tend livestock feed a world population of approximately 6.5 billion. Fifty years ago, the planet could not have sustained such a large population, and according to present projections, farmers will have to feed nine billion people by 2050. The greatest agricultural revolution in history has occurred in the last fifty years, with farmers in the United States leading the way. America's declining number of farms, however, comes as a surprise to many and may have dramatic implications. Paul K. Conkin's.